Morfologia e anatomia foliar de Asteraceae do bioma Pampa (Campos de Areais), Rio Grande do Sul, Brasil - Liesenfeld, Vanessa (2018)
Asteraceae is the largest family among the angiosperms and occurs predominantly in tropical regions and mainly in grassland area. In Brazil, it is one of the most diverse families, highlighting mainly the floristic of the Pampa biome, which in the country is restricted to Rio Grande do Sul. In the sand-fields, one of the phytophysiognomies of the Pampa biome (southwest RS) Asteraceae is also the richest family. The sand-fields vegetation occurs under sandy soils susceptible to the sandy stone process. This process is, a natural phenomenon (manintensified) that replaces the native vegetation cover by exposed substrate due to erosion and the action of the wind that rework the sandstone depositing the sand on the surface and promoting the constant mobility of sediments. In addition to the reduced fertility and water retention capacity of this sandy soil, poor distribution of rainfall, intense light and strong winds condition the vegetation of this region to extreme and limiting circumstances. Therefore, this study aimed to describe morphoanatomy and to identify adaptive characteristics that allow the survival of Asteraceae species in this adverse site. In addition to phylogenetically constant characters in the family (amphistomatic leaves, dorsiventral mesophyll, secretory channels and morphological diversity of trichomes), foliar morphoanatomy of the studied species indicates the predominant occurrence of adaptive characteristics to xeric environments that protect mainly against high luminosity and water scarcity: reduced leaves and coriaceous, tomentose indumentum, cuticle and thickened epidermal cells, epicuticular wax, amphistomatic leaves and investment in photosynthetic and support tissue. Although it occupies the same habitat and is under the influence of the same environmental conditions, each species develops a distinct adaptive strategy to survive and, therefore, their resistance or tolerance results from the interaction of several factors throughout the life history of the plants.